Aronia (Aronia melanocarpa) Polyphenols Modulate the Microbial Community in a Simulator of the Human Intestinal Microbial Ecosystem (SHIME) and Decrease Secretion of Proinflammatory Markers in a Caco‐2/endothelial Cell Coculture Model. Issue 22 (10th October 2018) - Wu, Ting; Grootaert, Charlotte; Pitart, Judit; Vidovic, Nevena Kardum; Kamiloglu, Senem; Possemiers, Sam; Glibetic, Maria; Smagghe, Guy; Raes, Katleen; Van de Wiele, Tom; Van Camp, John
Abstract : Scope: To explore the mechanisms behind the health effects of Aronia ( Aronia melanocarpa ), the microbial community modulating and anti‐inflammatory effects of Aronia polyphenols are investigated by combining the similutor of the human intestinal microbial ecosystem (SHIME) with a coculture of intestinal and endothelial cells. Results: Administration of Aronia juice (6.5g L –1 ) to the SHIME for 2 weeks increases the abundance of firmicutes to 92% in the ascending colon (AC), 85% in the transverse colon (TC), and 82% in the descending colon (DC; p  < 0.001), proteobacteria (6.7% in AC, p  < 0.001), and Akkermansia (14% in TC and 18% in DC, p  < 0.001) and decreases the abundance of Bifidobacterium species, associated with a decrease of acetate and increase of propionate and butyrate, whereas no significant difference is observed upon placebo juice treatment. After addition of the digests to TNF‐α challenged Caco‐2/endothelial cocultures, intercellular adhesion molecule (ICAM)‐1, IL‐8, and monocyte chemoattractant protein‐1 levels are significantly downregulated. Interestingly, Aronia juice treats digests from each colon compartment resulting in a stronger decrease of the ICAM‐1 secretion (up to 73%, p  < 0.001) compared to their corresponding placebo treated digests, thereby pointing to a polyphenol‐dependent effect. Conclusions: Aronia polyphenols modulate intestinal microbial composition, induce beneficial short chain fatty acid production, and prevent inflammatory stress in endothelial cells. This opens perspectives for the use of Aronia polyphenols as prebiotics in the context of intestinal and cardiovascular health. Abstract : Aronia juice increases abundance of firmicutes, proteobacteria and Akkermansia, decreases the abundance of Bifidobacterium species, associates with a decrease of acetate and increase of propionate and butyrate in the simulator of the human intestinal microbial ecosystem (SHIME). Aronia digests significantly decrease pro‐inflammatory markers (ICAM‐1, IL‐8 and MCP‐1) in to TNF‐α challenged intestinal/endothelial cell‐based co‐cultures.